THE EFFECT OF AUDIT COMMITTEE, LEVERAGE, RETURN ON ASSETS, COMPANY SIZE, AND SALES GROWTH ON TAX AVOIDANCE - Fauzan, Fauzan; Ayu, Dyah Ayu; Nurharjanti, Nashirotunnisa (Riset Akuntansi dan Keuangan Indonesia, 2019)
The purpose of this research is to analyze the effect of effect of audit committee, leverage, return on assets, company size, and sales growth of tax avoidance. The population in this research is  a manufacturing company listed in Indonesia Stock Exchange (IDX) period 2014-2016. The sample is determined by purposive sampling technique and obtained sample of 60 companies. This research uses multiple regression data analysis techniques. The result in this research is audit commitee, leverage, return on assets, company size, and sales growth influence to tax avoidance.